Antimicrobial activity of phenolic compounds identified in wild mushrooms, SAR analysis and docking studies - Alves, Maria José (2013)
Aim and Methods: Although the antimicrobial activity of extracts from several mushroom species have been reported, studies with the individual compounds present in that extracts are scarce. Herein, the antimicrobial activity of different phenolic compounds identified and quantified in mushroom species from all over the world was evaluated. Furthermore, a structure activity relationship (SAR) analysis and molecular docking studies were performed, in order to provide insights in the mechanism of action of potential antimicrobial drugs for resistant microorganisms. Results: 2,4-Dihydroxybenzoic and protocatechuic acids were the phenolic compounds with higher activity against the majority of Gram negative and Gram positive bacteria. Furthermore, phenolic compounds inhibited more MRSA than methicillin sensible Staphylococcus aureus. MRSA was inhibited by 2,4-dihydroxybenzoic, vanillic, syringic (MICs=0.5 mg/mL) and p-coumaric (MIC= 1 mg/mL) acids, while these compounds at the same concentrations had no inhibitory effects against methicillin sensible Staphylococcus aureus. Conclusions: The presence of carboxylic acid (COOH), two hydroxyl (OH) groups in para and ortho positions of the benzene ring, as also a methoxyl (OCH3) group in the meta position seems to be important for anti-MRSA activity. Significance and Impact of the Study: Phenolic compounds could be used as antimicrobial agents, namely against some microorganisms resistant to commercial antibiotics.